The body in bioethics - Campbell, Alastair V. (London : Routledge, 2009)
The author explores different views of the significance of the human body and contrasts those which regard it as a commodity or personal possession with those which stress its moral value as integral to the personal identity of individuals. This study provides background to many of the controversies in medical ethics.
Why the body matters -- My body : property, commodity or gift? -- Body futures -- The tissue trove -- The branded body -- Gifts from the dead -- Together at last.
Includes bibliographical references (p. [133]-144) and index.
Keywords: Medical ethics; Bioethics; Human body -- Moral and ethical aspects